The roles of WNT1 and DKK1 during in vitro neural differentiation of mouse embryonic stem cell lines - Gao, Liyang (2013)
Embryonic stem cells (ESCs) possess two unique properties: self-renewal and pluripotency. These unique properties make ESCs useful tools to discover the mechanisms behind differentiation and development, to unravel the mechanism of diseases, to test the effect of drugs as well as for use in clinical trials for degenerative disease and developmental defects. Large quantities of neurons or neural precursors are required for treating eurodegenerative diseases, hence understanding the mechanisms behind neural differentiation of ESCs and establishing the appropriate protocols in generating pure population of specific neuronal precursors are indeed essential. Lots of growth factors and cell signalling molecules have been found to play important roles during neural differentiation of ESCs. The Wnt/β-catenin pathway is one of the essential signalling pathways involved in neurogenesis in vivo and neural differentiation of ESCs in vitro. However, the activity of Wnt signalling during neural differentiation of ESCs is not constitutive but rather it is stage-dependent. The Wnt signalling pathway has been found to be downregulated upon the formation of neural precursor cells, and therefore is believed to inhibit neural differentiation of mESCs in vitro. Moreover, recently, the Wnt signalling pathway has also been found to regulate the self-renewal of mESCs in vitro. In this project, two inducible transgenic mESC lines carrying two important components of Wnt/β-catenin signalling pathways: Wnt1-HA and Dkk1 gene have been established and characterized. The system used was a binary system that combines two techniques; Cre/loxP-based genetic recombination and ligand-dependent activation of Cre. Expression of the transgene was induced upon exposure to a synthetic estrogen receptor, 4-hydroxytamoxifen (4’-OHT). Time course induction was carried out in both cell lines, each with two different clones, to obtain the optimal dosage of 4’-OHT in inducing the expression of the transgene. Cytotoxicity effects of non-detrimental dosage of 4’-OHT were also determined during neural differentiation of mocktransfected inducible ES cell system (CAG-floxed-neopA-empty vector). Using the system, I then aimed to unravel the effects of stimulating (through overexpression of Wnt1) and inhibiting (through overexpression of Dkk1) Wnt signalling pathway at specific time points during neural differentiation process on the formation of neural precursor cells and post-mitotic neurons. In addition, the system also allows the access to the role of Wnt1 in maintaining the self-renewability of undifferentiated mESCs in the absence of LIF through overexpression of Wnt1-HA in mESCs. It was found that 1) non-detrimental dosages of 4’-OHT and different induction time were needed to induce expression of Dkk1/Wnt1-HA transgenes (in mESCs - Dkk1: 200nM/48h; Wnt1-HA: 600nM/48h; and in embryoid bodies (EBs) – Dkk1:400nM/72h; Wnt1-HA: 1000nM/48); 2) overexpression of Wnt1 maintained self-renewal and neural commitment of mESCs; 3) Wnt1 promoted the formation of NPCs and post-mitotic neurons; 4) constitutive overexpression of Dkk1 inhibited the formation of NPCs; and interestingly, 5) overexpression of Dkk1 at early and later stages significantly increased the formation of NPCs and post-mitotic neurons (T-test, P<0.05). Results from this project confirm the multiple roles and stage-dependent of Wnt signal during neural differentiation process of mESCs in vitro as well as in maintaining the self-renewability of undifferentiated mESCs. It is hoped that the findings will add up to current knowledge regarding the understanding behind the differentiation process of ESCs, hence would be essential for future neurodegenerative cell-based therapy.